Application of the RE-AIM Framework for the Pediatric Mild Traumatic Brain Injury Evaluation and Management Intervention: A Study Protocol for Program Evaluation - Tucker, Paula W.; Bull, Rachel; Hall, Alex; Moran, Tim P.; Jain, Shabnam; Sathian, Usha; Simon, Harold K.; Gioia, Gerard A.; Ratcliff, Jonathan J.; Wright, David W. (Frontiers in Public Health, 2022)
Background: Children who experience a mild Traumatic Brain Injury (mTBI) may encounter cognitive and behavioral changes that often negatively impact school performance. Communication linkages between the various healthcare systems and school systems are rarely well coordinated, placing children with an mTBI at risk for prolonged recovery, adverse impact on learning, and mTBI re-exposure. The objective of this study is to rigorously appraise the pediatric Mild Traumatic Brain Injury Evaluation and Management (TEaM) Intervention that was designed to enhance diagnosis and management of pediatric mTBI through enhanced patient discharge instructions and communication linkages between school and primary care providers. Methods: This is a combined randomized and 2 x 2 quasi-experimental study design with educational and technology interventions occurring at the clinician level with patient and school outcomes as key endpoints. The RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) framework will be utilized as a mix methods approach to appraise a multi-disciplinary, multi-setting intervention with the intent of improving outcomes for children who have experienced mTBI. Discussion: Utilization of the RE-AIM framework complemented with qualitative inquiry is suitable for evaluating effectiveness of the TEaM Intervention with the aim of emphasizing priorities regarding pediatric mTBI. This program evaluation has the potential to support the knowledge needed to critically appraise the impact of mTBI recovery interventions across multiple settings, enabling uptake of the best-available evidence within clinical practice. Trial Registration: ClinicalTrials.gov Unique Identifier: NCT04576715